TANTANGAN MUSLIMAH DI ERA GLOBALISASI - Siame, Norma Dg. (Hunafa: Jurnal Studia Islamika, 2007)
Today, Moslem women and men have the same opportunity in education and job. This opportunity puts Moslem women in a dilemmatic position in term of performance. On one hand, they have to obey Islamic rules and culture. On the other hand, they have to follow culture development in term of physical performance and relationship with men. One way to minimize the impact of globalization, therefore, is by strengthening Islamic teaching in our life and in the way women interact with men.Â Kata Kunci: tantangan muslimah, era globalisasi, ajaran Islam